2014
DOI: 10.17061/phrp2511408
|View full text |Cite
|
Sign up to set email alerts
|

Applying a performance monitoring framework to increase reach and adoption of children’s healthy eating and physical activity programs

Abstract: The allocation of a significant amount of new funding for health promotion in Australia through the National Partnership Agreement on Preventive Health (2009-14) created a unique opportunity to implement a comprehensive approach to the prevention of chronic diseases and demonstrate significant health improvements. Building on existing health promotion infrastructure in Local Health Districts, the NSW Ministry of Health adopted a scaled-up state-wide capacity-building model, designed to alter policies and pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…1822, 2430, 32, 34, 35 Two of the three practice-based evidence cases were from LMICs. 31, 33 Fourteen of the cases described an intervention that fit into one of the seven categories of investment in physical activity (Figure 1), with the most frequently represented categories being those of community-wide programs (n=6), 20, 22, 24, 31, 32, 34 ‘whole of school’ programs (n=3), 23, 2628, 30 and physical activity promotion or NCD prevention integrated into the health care system (n=3). 18, 25, 29 No cases relating to the categories of transport systems prioritising active travel, or urban design policies and infrastructure, were identified.…”
Section: What Can We Learn About Scaling Up Physical Activity Intementioning
confidence: 99%
See 2 more Smart Citations
“…1822, 2430, 32, 34, 35 Two of the three practice-based evidence cases were from LMICs. 31, 33 Fourteen of the cases described an intervention that fit into one of the seven categories of investment in physical activity (Figure 1), with the most frequently represented categories being those of community-wide programs (n=6), 20, 22, 24, 31, 32, 34 ‘whole of school’ programs (n=3), 23, 2628, 30 and physical activity promotion or NCD prevention integrated into the health care system (n=3). 18, 25, 29 No cases relating to the categories of transport systems prioritising active travel, or urban design policies and infrastructure, were identified.…”
Section: What Can We Learn About Scaling Up Physical Activity Intementioning
confidence: 99%
“…The remaining cases involved health education delivered by telephone or text message. 19, 21 Six cases described interventions targeting children or youth, 18, 23, 2528, 30, 33 while four focused on adults, 19, 24, 29, 35 one on older adults, 32 and another one on both adults and older adults. 34 Two cases related to all age groups 21, 22 and two were not specific about age groups.…”
Section: What Can We Learn About Scaling Up Physical Activity Intementioning
confidence: 99%
See 1 more Smart Citation
“…Such research has typically been non‐experimental and focused on characteristics of the program (or intervention), organisational capacity, or broader contextual factors as correlates of sustained implementation fidelity 2 . Research suggests that establishment of systems, processes and structures within organisations adopting new health programs, and building of organisational readiness and capacity that occur as part of initial implementation efforts may facilitate sustained program implementation 7 . While this research has provided important formative work for the field, to maximise the benefits of investments in population‐wide program implementation, policy makers and practitioners are primarily interested in whether planned investments are sufficient to maintain long‐term program implementation or whether ongoing investment is required to achieve this outcome.…”
mentioning
confidence: 99%
“…While public health history is littered with examples of effective public health programs that were discontinued when external funds to support implementation have ceased or following attempts to transfer responsibility for ongoing program delivery, 6 a number of case studies in Australia and elsewhere have demonstrated that sustained implementation of public health programs is possible 6,7,12 . Developing an understanding of the success factors for such cases is important.…”
mentioning
confidence: 99%